KAJIAN GEOGRAFI TERHADAP MATA PENCAHARIAN PENDUDUK DI NAGARI MUARO PANEH KECAMATAN BUKIT SUNDI KABUPATEN SOLOK - Ine Sentia; Widya Prarikeslan (JURNAL BUANA, 2021)
This study aims to find out the Geographic Study on Population Prevention Point in Nagari Muaro Paneh Bukit Sundi District Solok Regency. The type of research was conducted in Nagari Muaro Paneh, Bukit Sundi District, Solok Regency. The time used by researchers for this study was carried out since the date of the research permit was issued in approximately 2 months. The population in this study were all residents of Nagari Muaro Paneh many as 2835 families. The sampling of respondents in this study was taken based on the Slovin formula many as 44 people. For this sampling, it was carried out through incidental sampling techniques. The data sources in this study were primary data and secondary data. Data collection in this study used the observation method of interview documentation. This study uses a percentage formula. The result of the research show that a geographic study of the livelihoods of the population in Nagari Muaro Paneh, Bukit Sundi District, Solok Regency is based on location, the livelihoods of the population in Nagari Muaro Paneh, Bukit Sundi District, Solok Regency dominate rice fields, namely 47,73 % and trading 34,09%. The distance traveled to work a lot is still around Nagari Muaro Paneh, generally it is about 2 Km, which is 27,27%. Morphology of land or place of work of resident in Nagari Muaro Paneh, Bukit Sundi District, Solok Regency is on a flat surface, which is 95,45%, because the paddy farmland located in Nagari Muaro Paneh dominates flat land and rainfalls. The livelihood pattern of the resident in Nagari Muaro Paneh Bukit Sundi District Solok Regency is central and spread, namely by 50%.